BEYOND ISLAM-MALAY: Hegemony, Exclusion, and Decolonial Resistance in Riau - Hanafi, Imam; Wan Yusoff, Wan Zahari bin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The narrative of “Islam is Malay, and Malay is Islam” has become a dominant identity construct in Riau. This article unpacks how such a narrative operates as a hegemonic discourse that excludes non-Muslim Indigenous communities—such as the Akit, Talang Mamak, and Anak Rawa peoples—from being recognized as part of the